vVo2max and tlimVo2max: Practical considerations for triathletes on a quest for speed - Modave, F.
The author will first describe how to determine vVo2max, tlimVo2max and also a short cut for very busy athletes, or athletes who already have a pretty good idea of their vVo2max. These tests are easy to do and are field tests. You will not have to go to a lab and spend some big bucks! Then, the autor will describe the workouts you can design, and eventually it is shown how to integrate these sessions in your training phase depending on the sort of triathlon you are competing in. Contents: - Introduction - Determining vVo2max and tlimVo2max - Improving your vVo2max and tlimVo2max (and other variables) . The typical 30-30 session in running . Adapting this session to swimming and cycling . other sessions - Scheduling these sessions in the season for short course and long course triathletes